Features of using innovative technologies in teaching English language in higher education institutions. - Kharkevych, Halyna; Kruhlij, Olena; Pechko, Nina; Sobol, Nataliia; Shyba, Alona (Revista Eduweb, 2024)
The peculiarities of using innovative technologies in teaching English in institutions of higher education have been clarified. The meaning of the concepts "innovation" and "educational innovation" is revealed. The main criteria of manufacturability, which must be met by pedagogical innovation technology, are shown. The main principles by which innovative activities are carried out in institutions of higher education are highlighted. Approaches containing innovative technologies in teaching English are disclosed. The most effective innovative technologies are grouped and effective technologies for teaching English are considered. that deserve attention in teaching English in institutions of higher education (interactive learning technology, distance learning, multimedia technologies, virtual environment technology). Taking into account the peculiarities of the use of innovative technologies in teaching English in higher education institutions, microlearning (bite-sized learning) technology attracts attention, the content and advantages of which are shown in the article. The advantages of using innovative technologies in teaching English in higher education institutions are shown. The main tasks in high-quality English language teaching are the development of the following basic skills: reading, listening, communication, and writing. The role of each individual skill is shown and the content of technologies that can be applied for improvement and development is revealed.
Keywords: innovations, innovative technologies, educational innovation, teaching English, institutions of higher education.